2008
DOI: 10.1038/nm1784
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a noncoding RNA is elevated in Alzheimer's disease and drives rapid feed-forward regulation of β-secretase

Abstract: Recent transcriptomics efforts have revealed that numerous protein-coding messenger RNAs have natural antisense transcript partners, most of which seem to be noncoding RNAs. Here we identify a conserved noncoding antisense transcript for β-secretase-1 (BACE1), a crucial enzyme in Alzheimer's disease pathophysiology. The BACE1-antisense transcript (BACE1-AS) regulates BACE1 mRNA and subsequently BACE1 protein expression in vitro and in vivo. It seems that the argument for concordant regulation can only be made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
1,070
3
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,286 publications
(1,106 citation statements)
references
References 51 publications
28
1,070
3
5
Order By: Relevance
“…They can act as decoys by binding to RNA or protein and titrating these away from other molecules; they can act as guides to direct localisation of ribonucleoprotein complexes; and they can act as scaffolds and structural platforms for nuclear processes. Aberrant expression of lncRNAs have been associated with various human conditions, including those as diverse as cancers (Yu et al, 2012), myocardial infarction (Ishii et al, 2006a) and Alzheimer"s disease (Faghihi et al, 2008). lncRNAs have been…”
Section: ) Authors Should Consider Whether the Discordance Between Mmentioning
confidence: 99%
“…They can act as decoys by binding to RNA or protein and titrating these away from other molecules; they can act as guides to direct localisation of ribonucleoprotein complexes; and they can act as scaffolds and structural platforms for nuclear processes. Aberrant expression of lncRNAs have been associated with various human conditions, including those as diverse as cancers (Yu et al, 2012), myocardial infarction (Ishii et al, 2006a) and Alzheimer"s disease (Faghihi et al, 2008). lncRNAs have been…”
Section: ) Authors Should Consider Whether the Discordance Between Mmentioning
confidence: 99%
“…To investigate whether the overlapping 3′UTR of WDR83 and DHPS RNA duplex affected the stability of the mRNA, we blocked any new mRNA synthesis with α-amanitin (an RNA polymerase II inhibitor) and analyzed the expression of WDR83, DHPS, GAPDH and 18S RNA over a 24-h period. 18S RNA, which was a product of RNA polymerase I and was unchanged after α-amanitin treatment, served as the internal control [9]. As shown in Figure 5C, compared with control siRNAs, treatment with the specific siRNAs against DHPS resulted in a decreased stability of WDR83 mRNA; WDR83 knockdown also caused a reduced stability of DHPS mRNA.…”
Section: Dhps and Wdr83 Formed An Rna Duplex And Mutually Increased Tmentioning
confidence: 99%
“…It was reported that the RNA-RNA duplex could protect mRNA from RNase degradation and enhance mRNA stability [9,20]. To investigate whether the overlapping 3′UTR of WDR83 and DHPS RNA duplex affected the stability of the mRNA, we blocked any new mRNA synthesis with α-amanitin (an RNA polymerase II inhibitor) and analyzed the expression of WDR83, DHPS, GAPDH and 18S RNA over a 24-h period.…”
Section: Dhps and Wdr83 Formed An Rna Duplex And Mutually Increased Tmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are only a few cases showing that editing can influence miRNA or siRNA biogenesis and target recognition, and the function of edited lncRNAs is still unclear. Moreover, non-coding RNAs are associated with cancer [13][14][15], Prader-Willi syndrome [16,17], autism [18,19], and Alzheimer's disease [20], but no evidence shows that edited non-coding RNAs are related to human disease. ADARs are highly expressed in brain tissue, thus edited non-coding RNAs most likely play a regulatory role in brain development, functional diversification, and neurological disease.…”
Section: Prospects and Conclusionmentioning
confidence: 99%